2021
DOI: 10.5603/pjnns.a2021.0017
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Polestar N30 low-field MRI system for resecting non-enhancing intra-axial brain lesions

Abstract: Background. To determine the utility of an intraoperative magnetic resonance imaging (iMRI) system, the Polestar N30, for enhancing the resection control of non-enhancing intra-axial brain lesions.Materials and methods. Seventy-three patients (60 males [83.3%], mean age 37 years) with intra-axial brain lesions underwent resection at Sheba Medical Centre using the Polestar between February 2012 and the end of August 2018. Demographic and imaging data were retrospectively analysed. Thirty-five patients had a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Our systematic review process screened 525 articles and, after evaluating the titles, abstracts, and full text, 21 of them were selected for inclusion in the final analysis. [3,6,7,[12][13][14]16,18,[21][22][23][25][26][27][28]32,33,35,36,38,39] e articles were screened and quality assessed independently by JM and AB, and any discrepancies were resolved by AA. e screening process and quality assessment procedure are thoroughly delineated in Figure 1 of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart, and Tables 1a and b, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our systematic review process screened 525 articles and, after evaluating the titles, abstracts, and full text, 21 of them were selected for inclusion in the final analysis. [3,6,7,[12][13][14]16,18,[21][22][23][25][26][27][28]32,33,35,36,38,39] e articles were screened and quality assessed independently by JM and AB, and any discrepancies were resolved by AA. e screening process and quality assessment procedure are thoroughly delineated in Figure 1 of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart, and Tables 1a and b, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to note that this came at the expense of a longer surgical duration. Wu et al 2009 [36] ✩✩✩✩ ✩✩ ✩✩ Kim et al 2013 [13] ✩✩✩ ✩✩ ✩✩ Makary et al 2011 [18] ✩✩✩✩ ✩ ✩ White et al 2018 [35] ✩✩✩✩ ✩ ✩ García et al 2017 [8] ✩✩✩ ✩✩ ✩✩ Bohinski et al 2001 [3] ✩✩✩ ✩ ✩✩ Nimsky et al 2003 [21] ✩✩✩✩ ✩✩ ✩ Kırış and Arıca 2011 [14] ✩✩✩ ✩ ✩✩✩ Hlavica et al 2013 [12] ✩✩✩ ✩✩ ✩✩✩ iabpha and Hansasuta 2016 [32] ✩✩✩ ✩ ✩ Livne et al 2014 [16] ✩✩✩✩ ✩✩ ✩✩ Senft et al 2010 [26] ✩✩✩ ✩✩ ✩✩ Nimsky et al 2003 [22] ✩✩✩ ✩ ✩✩✩ Senft et al 2008 [27] ✩✩✩ ✩✩ ✩✩✩ Zimmermann et al 2001 [39] ✩✩✩ ✩ ✩✩ Zimmermann et al 2000 [38] ✩✩✩ ✩ ✩✩ Czyż et al 2011 [7] ✩✩✩ ✩✩ ✩✩ Buchfelder et al 2002 [6] ✩✩✩ ✩✩ ✩✩✩ Senft et al 2010 [28] ✩✩✩ ✩✩ ✩✩ Ungar et al 2021 [33] ✩✩✩ ✩✩ ✩✩ ✩: 1 point, ✩✩: 2 points, ✩✩✩: 3 points, ✩✩✩✩: 4 points Our review revealed that the use of low-field IMRI has been associated with a significant increase in the number of patients who achieved GTR of brain tumors. Attaining GTR is of paramount importance, as it has been shown to be associated with prolonged survival in various brain tumor types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Why do you think that happened?”), our results suggest the possibility that more frequent conversation (in all contexts, not just television viewing) can promote imaginative expression (one of the underpinnings of curiosity [ 56 ]) at kindergarten. Interventions to promote dialogic exchanges and language-rich caregiver-child interactions have been shown to be beneficial for early imagination and learning, and may be similarly promotive for early childhood curiosity [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%